The Effect of Social Media on Student Learning: Chances and Challenges - Yogi, Chatreys Suci Ramadani; Aimah, Siti (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Social media plays an important role in student learning, offering a range of opportunities to access information in a fast and engaging way. However, uncontrolled use also presents challenges that can affect learning. This research aims to analyze the influence of social media on current students' learning styles, highlighting the opportunities that can be leveraged to support the learning process as well as the challenges that need to be overcome to minimize its negative impact. The research was conducted at Nahdlatul Ulama Sudirman Vocational High School. This research used a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and document analysis, and involved students, teachers, and the principal as the main participants. The results show that social media provides significant benefits in supporting independent learning, expanding access to information, and facilitating collaboration between students. However, distraction from irrelevant content is the main obstacle that affects learning focus. The implication of this study emphasizes the importance of digital literacy, time management, and guidance from teachers to optimize the use of social media as a learning tool. This research provides insights for educators in designing learning strategies that are relevant to students' needs in the digital era.